Effect of soaking Allium sativum peel waste on microbial contamination of salted anchovy rice and analysis of its total phenolic content - Iramie Duma Kencana Irianto; Amelia Handayani Burhan; Afifah Astuti (Jurnal Penelitian Saintek, 2026)
Approximately 84% of salted anchovy rice fish sold in traditional markets in Yogyakarta still contain formaldehyde, a hazardous substance that may cause adverse health effects ranging from throat irritation to cancer. Saponin compounds contained in Allium sativum peel waste have been reported to reduce formaldehyde levels in salted anchovy rice fish by up to 89.12%; however, the reduction of formaldehyde may increase microbial contamination. This study aimed to examine microbial contamination in salted anchovy rice fish after immersion treatment using A. sativum peel waste. Qualitative analysis of saponins was conducted using the Froth test and Thin Layer Chromatography (TLC), while phenolic compounds were analyzed qualitatively using TLC and quantitatively using spectrophotometric methods. Microbial contamination was evaluated using the Total Plate Count (TPC) method. The results demonstrated that A. sativum peel waste contained saponin and phenolic compounds, with an average phenolic content of 8.57 ppm. Furthermore, 1 g of A. sativum peel waste reduced microbial contamination in salted anchovy rice fish by up to 10,000-fold. The microbial contamination level showed a TPC value of 8.55 × 10³ colonies/g, indicating that the product remained within the safe consumption limit of less than 1 × 10⁵ colonies/g.